Respuesta :

Answer:

Step-by-step explanation:

Considering the given triangle KFP, to determine FP, we would apply the sine rule. It is expressed as

a/SinA = b/SinB = c/SinC

Where a, b and c are the length of each side of the triangle and angle A, Angle B and angle C are the corresponding angles of the triangle. Likening it to the given triangle, the expression becomes

FP/SinK = FK/SinP = KP/SinF

Therefore

FP/Sin 49 = 66/Sin 85

Cross multiplying, it becomes

FPSin85 = 66Sin49

0.996FP = 45 × 0.7547

0.996FP = 33.9615

FP = 33.9615/0.996

FP = 34.1

ACCESS MORE